2022
DOI: 10.1186/s12302-022-00634-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of fine particulate matter (PM2.5) on hospital admissions for cardiovascular diseases in Lanzhou, China: a time-series study

Abstract: Background Up until now, evidence pertaining to the short-term effects of fine particulate matter (PM2.5) in cardiovascular diseases (CVD) is scarce in China. In this study, we aim to estimate the association between short-term exposure to PM2.5 and hospitalizations for total and cause-specific CVD in Lanzhou of China. Methods Daily counts of cardiovascular admissions were obtained from three large general hospitals in Lanzhou, China between 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…According to some studies, men are more vulnerable to pollution than women. This is because male smoking rates were substantially greater in some areas, making the individuals more sensitive towards PM 10 [15]. In addition to this study, a few other studies [15,20,24] agreed that this inconsistency was caused by several factors.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…According to some studies, men are more vulnerable to pollution than women. This is because male smoking rates were substantially greater in some areas, making the individuals more sensitive towards PM 10 [15]. In addition to this study, a few other studies [15,20,24] agreed that this inconsistency was caused by several factors.…”
Section: Discussionsupporting
confidence: 59%
“…This is because male smoking rates were substantially greater in some areas, making the individuals more sensitive towards PM 10 [15]. In addition to this study, a few other studies [15,20,24] agreed that this inconsistency was caused by several factors. The factors that needed to be highlighted were diverse physiological characteristics in both genders, routine activities, smoking habits, occupations, comorbidity factors and others.…”
Section: Discussionsupporting
confidence: 59%
“…The additional women-to-men ratio of RR (RRR) was 1.05 (95% CI, 1.02–1.08) per 10 μg/m 3 increment in PM 2.5 exposure. Wu et al [ 90 ] conducted a time-series study to estimate the link between short-term PM 2.5 exposure and CVD-related hospitalizations in Lanzhou, China, and showed that short-term PM 2.5 exposure increased the hospitalizations for total CVD, especially IHD in male and elderly populations. Another recent open cohort study [ 91 ] was conducted to investigate the associations between long-term PM 2.5 exposure and cardiovascular events as well as CVD-specific mortality among hemodialysis patients in the U.S. A PM 2.5 level of 1 μg/m 3 was associated with an increased risk of cardiovascular events (1.02, 95% CI: 1.01, 1.02) and CVD-specific mortality (1.02, 95% CI: 1.02, 1.03).…”
Section: Epidemiological Studies On the Short- And Long-term Effects ...mentioning
confidence: 99%
“…Lanzhou City is a river-valley type city, and the terrain is characterized by a narrow east–west direction and a narrow north–south direction facing the mountains. Residential areas are mainly concentrated on both sides of the city roads, and the location of the air quality monitoring station is not more than 15 km away from the residential areas [ 29 , 30 ]. Therefore, the monitoring data from the air quality testing station can well represent the exposure concentration of the residents.…”
Section: Methodsmentioning
confidence: 99%